A Promising Approach for Controlling the Second Coordination Sphere of Biomimetic Metal Complexes: Encapsulation in a Dynamic Hydrogen‐Bonded Capsule. Issue 1 (30th November 2020) - Zhang, Tongtong; Le Corre, Laurent; Reinaud, Olivia; Colasson, Benoit
Abstract: The design of biomimetic models of metalloenzymes needs to take into account many factors and is therefore a challenging task. We propose in this work an original strategy to control the second coordination sphere of a metal centre and its distal environment. A biomimetic complex, reproducing the first coordination sphere, is encapsulated in a self‐assembled hydrogen‐bonded capsule. The cationic complex is co‐encapsulated with its counter‐anion or with solvent molecules. The capsule is dynamic, allowing a fast in/out exchange of the co‐encapsulated species. It also provides both a hydrogen‐bonding site in the second coordination sphere and a source of proton as it can be deprotonated in the presence of the complex, providing a globally neutral host‐guest assembly. This simple and broad scope strategy is unprecedented in biomimetic studies. The approach appears to be a very promising method for the stabilisation of reactive species and for the study of their reactivity. Abstract : A better model : The encapsulation of a coordination complex in a dynamic hydrogen bonded capsule exhibits several features present in metalloenzymes such as the isolation of the metal centre from the bulk solvent while maintaining guest exchanges, a well‐defined second coordination sphere, and acid/base residues close to the metal centre.